Temporal and regional alterations in NMDA receptor expression in Mecp2-null mice - Blue, Mary E. (2011)
Our previous postmortem study of girls with Rett Syndrome (RTT), a development disorder caused by MECP2 mutations, found increases in the density of NMDA receptors in the prefrontal cortex of 2–8 year-old girls, while girls older than 10 years had reductions in NMDA receptors compared to age matched controls (Blue et al., 1999b). Using [(3)H]-CGP to label NMDA type glutamate receptors in 2 and 7 week old wildtype (WT), Mecp2-null and Mecp2-heterozygous (HET) mice (Bird model), we found that frontal areas of the brain also exhibited a bimodal pattern in NMDA expression, with increased densities of NMDA receptors in Mecp2-null mice at 2 weeks of age, but decreased densities at 7 weeks of age. Visual cortex showed a similar pattern, while other cortical regions only exhibited changes in NMDA receptor densities at 2 weeks (retrosplenial granular) or 7 weeks (somatosensory). In thalamus of null mice, NMDA receptors were increased at 2 and 7 weeks. No significant differences in density were found between HET and WT mice at both ages. Western blots for NMDAR1 expression in frontal brain showed higher levels of expression in Mecp2-null mice at two weeks of age, but not at 1 or 7 weeks of age. Our mouse data support the notion that deficient MeCP2 function is the primary cause of the NMDA receptor changes we observed in RTT. Furthermore, the findings of regional and temporal differences in NMDA expression illustrate the importance of age and brain region in evaluating different genotypes of mice.